The effect of feed pretreatment on membrane microfiltration of titanium dioxide suspensions by ceramic tubular membranes - Grulich, Miroslav; Mikulášek, Petr (University of Pardubice, 2015)
The influence of a coagulant type and operating parameters on crossflow microfiltration of aqueous dispersions of titanium dioxide has been examined. The experiments were carried out with a tubular ceramic microfiltration membrane of nominal pore size 0.1 μm at various operating parameters. Three chosen types of organic coagulants were used for a series of crossflow microfiltration experiments: polyacrylamide (PAM), poly(diallyldimethylammonium chloride) (pDADMAC) and poly(acrylamide-co-acrylic acid) partial sodium salt (PACA). The value of steady-state permeate flux has been experimentally evaluated for the crossflow microfiltration with and without pretreatment. The results of the experiments without coagulants have shown that initial flux declines rapidly, but after an initial decline, the flux is stabilised. The results also suggest that pDADMAC is a better coagulant for this system and its optimum concentration is 30 mg l–1. Finally, it is shown that the feed pretreated by pDADMAC has resulted in more than three-times higher permeate flux than that without any pretreatment. Moreover, there was a very positive effect of this coagulant on the particle size. Pretreatment by 30 mg l–1 pDADMAC has led to almost eighteen-times higher average particle size compared to the average particle size without pretreatment. The other two coagulants did not show such improvements as pDADMAC; pretreatment of the feed by PAM giving only a 10 % higher permeate flux whilst the pretreatment of the feed by PACA causing even lower permeate flux than those without any pretreatment. Thus, the individual experiments have suggested us the need for careful selection of coagulants, because of their different impact upon the permeate flux.